2015
DOI: 10.1200/jop.2014.000661
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalists on an Inpatient Tertiary Care Oncology Teaching Service

Abstract: Purpose: Hospitalists provide quality care in various inpatient settings, but the ability of hospitalists to provide quality inpatient care for patients with complex cancer has not been studied. This study explores outcomes with a hospitalist-led versus medical oncologist-led house staff team on an inpatient medical GI oncology teaching service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…A separate study of patients with gastrointestinal cancer found that the most common reasons for unplanned hospitalization were fluid and electrolyte disorders, intestinal obstruction, and pneumonia . Among our patients on the gastrointestinal oncology service, fever and pain were the 2 most common reasons for hospitalization . The underlying natural disease course of cancer also deserves attention, and it is useful for patients and their families to understand this context.…”
Section: Practical Guidelines For Coordinating Care In Hospitalized Pmentioning
confidence: 87%
See 1 more Smart Citation
“…A separate study of patients with gastrointestinal cancer found that the most common reasons for unplanned hospitalization were fluid and electrolyte disorders, intestinal obstruction, and pneumonia . Among our patients on the gastrointestinal oncology service, fever and pain were the 2 most common reasons for hospitalization . The underlying natural disease course of cancer also deserves attention, and it is useful for patients and their families to understand this context.…”
Section: Practical Guidelines For Coordinating Care In Hospitalized Pmentioning
confidence: 87%
“…In addition to being board certification in internal medicine, 1 member is board certified in medical oncology and 4 members are board certified in hospice and palliative medicine. In a recent article, we describe our experience with patients on our inpatient gastrointestinal oncology service; patients with pancreatic cancer accounted for a quarter of all inpatient admissions, and 90% of all patients had been diagnosed with metastatic disease …”
Section: Hospital Medicine At Mskccmentioning
confidence: 99%
“…common cancer-related complications related to systemic therapy, progression of disease, and end of life, have already created value in inpatient oncology by reducing length of stay and average costs per patient. 15,26,27 We believe that a similar model of provider subspecialization in the OECC can provide further value through not only more efficient, cost-effective delivery of urgent care but also reduced overall admission rates compared with those historically observed in EDs.…”
Section: Discussionmentioning
confidence: 99%
“…The hospitalist model of inpatient care delivery is an accepted standard of care [1,2], and there are now numerous examples of hospitalists managing hospitalized patients with cancer, with similar outcomes to those cared for on medical oncologist-led services [3][4][5][6][7]. The perceptions of oncologists about inpatient cancer care delivery and the hospitalist model are unknown.…”
Section: Introductionmentioning
confidence: 99%